Hubungan Karasteristik, Pengetahuan,Sikap Dan Tindakan Penderita Tuberkulosis Paru Dengan Kepatuhan Minum Obat Dipuskesmas Simpang Dolok Batu Bara - Masna Maria Sinambela; Sondang Sidabutar; Yunardi Yunardi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the relationship between characteristics, knowledge, attitudes, and actions of Pulmonary Tuberculosis patients with medication adherence at Simpang Dolok Health Center, Batu Bara Regency. The study design used a quantitative approach with the Spearman correlation method to measure the relationship between variables. The number of respondents was 35 people selected purposively. The results showed that the knowledge variable did not have a significant relationship with medication adherence (r = -0.056; p = 0.748), while the attitude and action variables had a significant and positive relationship with adherence (attitude: r = 0.641; p = 0.000 and action: r = 0.568; p = 0.000). These findings indicate that the formation of positive attitudes and real actions of patients play a key role in the success of Pulmonary TB treatment, while knowledge alone is not enough. Therefore, health promotion interventions should be focused on strengthening attitudes and assisting patient actions so that compliance can be optimally improved.